(untitled) (Archaeologia Adriatica, 2017)
This paper discusses the notable, but unfortunately lost Naronitan tombstone CIL 3, 8438 with dona militaria and centurion insignia on the front side. It describes the interesting way in which the tombstone was lost, as well as its typological classification, pointing out an iconographic element that has remained unnoticed (a vitis), and finally proposing a dating for it. At the same time, it touches upon the complex subject matter of the unit in which the deceased served at the time of his death, i.e. the question of whether the Camp. cohort without or with the ordinal number I was a single unit or two units.